Genetic Structuration According to Lucien Goldmann: Concepts and Procedural Mechanisms in the Context of Systematic Critique - Soltani, Farouk; Trabelsi, Ammar (LANGUAGE ART, 2024)
This study is embedded within the domain of interdisciplinary critical studies, offering both a historical and descriptive exploration of genetic structuration as conceptualized by Lucien Goldmann. We delve into the terminological intricacies and delineate the procedural mechanisms foundational to this contemporary critical methodology. By engaging with literary texts, this approach equips readers with the tools to analyze literary works through the lens of genetic structuration, assimilate its underlying concepts, apply its guiding principles, and discern the symbiotic relationship between the social context and literary visions embedded within the text.